The Madrasa in Asia Political Activism and Transnational Linkages - Noor, Farish A.; van Bruinessen, Martin; Sikand, Yoginder (ISIM Series on Contemporary Muslim Societies, 2008)
Since the rise of the Taliban and Al Qaeda, the traditional Islamic schools known as the madrasa have frequently been portrayed as hotbeds of terrorism. For much longer, the madrasa has been considered by some as a backward and petrified impediment to social progress. However, for an important segment of the poor Muslim populations of Asia, madrasas constitute the only accessible form of education. This volume presents an overview of the madrasas in countries such as China, Indonesia, Malayisia, India and Pakistan.